UTILIZATION OF TISSUE CULTURE VIDEOS TO IMPROVE STUDENT BIOLOGY LEARNING OUTCOMES - Supini Andil (Jurnal Pelita Pendidikan, 2021)
This study aims to improve student biology learning outcomes on tissue culture by using learning videos in Class XI IPA-2 SMA Negeri 1 Batang Kuis T.P 2018/2019. This research consists of the cycle I and cycle II. Each cycle consists of 4 stages, namely, planning, implementing actions, observing, and reflecting. The subjects of this study were students of class XI IPA-2, totaling 32 students. The data collection tool used is a learning outcome test. Based on the pre-test conducted on 32 students, there were 16 (50%) students who got low learning outcomes (unfinished) and as many as 16 students (50%) who were included in the complete category. Then, eight students (25%) were in the incomplete category and 24 students (75%) during the first cycle. Furthermore, during the second cycle, the students who got low learning outcomes were two students (17%), and those included in the complete category were 30 students (93%). There has been a significant increase. Thus it can be concluded that using tissue culture videos can improve student biology learning outcomes in class XI IPA-2 SMA Negeri 1 Batang Kuis T.P 2018/2019